2001
DOI: 10.1089/107632701753213156
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Use of Alginate Hydrogel as Schwann Cell Matrix

Abstract: The use of bioresorbable conduits supplemented with Schwann cells (SCs) is a promising tissue engineering technique to replace nerve grafting. Alginate hydrogel (AH), as a SC tissue engineering matrix, has many advantages over previously used matrices but has not been evaluated for this purpose. In this study, the viability and proliferation of SCs together with SC function in AH was evaluated in vitro. AlamarBlue cell assay was used to monitor the viability of SCs in AH and compared to SC viability in collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 43 publications
1
55
0
1
Order By: Relevance
“…Alginate is a naturally derived polymer, which has been wildly employed in dispensing-based biofabrication for various applications such as nerve tissue engineering [5,6] and bone tissue engineering [7,8], because of its good biocompatibility and ease gelation in the presence of calcium ions [5,9,10]. And calcium ions have been used to crosslink alginate in order to form hydrogel in dispensing-based biofabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…Alginate is a naturally derived polymer, which has been wildly employed in dispensing-based biofabrication for various applications such as nerve tissue engineering [5,6] and bone tissue engineering [7,8], because of its good biocompatibility and ease gelation in the presence of calcium ions [5,9,10]. And calcium ions have been used to crosslink alginate in order to form hydrogel in dispensing-based biofabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…Alginate has many applications in the food and pharmaceutical industries, and in medical research it has been used as a material for the sustained release of bovine serum albumin (BSA), fibroblast growth factor (FGF), immunoglobulin G (IgG), nerve growth factor (NGF), transforming growth factor (TGF-), TGF-, live cells, and more. [13][14][15] Alginate also has been used as scaffold material for tissue engineering applications, 16 has been used to encapsulate Schwann cells, 17 and most importantly to our research, has been shown to enhance elongation of amputated axons of infant rat spinal cords. [18][19][20] We have created a biodegradable fiber format capable of encapsulating a variety of biologically sensitive molecules and/or carrying drug-loaded microspheres or lipospheres.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Alternatively, the nerve guide can be filled with SCs in a supporting adhesive matrix. [12][13][14]17,28 Therefore, the effect of fibronectin coating of TMC and CL (co)polymers on the behavior of HSCs was also investigated.…”
Section: Introductionmentioning
confidence: 99%